A prospective analysis of sleep deprivation and disturbance in surgical patients. (March 2016) - Dolan, Ross; Huh, Jae; Tiwari, Neil; Sproat, Tom; Camilleri-Brennan, John
Abstract: Introduction: Sleep deprivation has a potentially deleterious effect on postoperative recovery. The aim of our prospective study was to identify the factors contributing to postoperative sleep deprivation and disturbance in order to recommend improvements in postoperative care. Methods: 102 consecutive patients attending for elective general and orthopaedic surgery were interviewed preoperatively (baseline) and postoperatively on their duration of sleep, number of wakenings during the night, factors contributing to sleep loss and the use of analgesia and night sedation. Results: Patients woke up a median of 5 times in the first postoperative night compared to a median of 3 times preoperatively (p = 0.01). Pain was the predominant factor preventing sleep, affecting 39% of patients preoperatively and 48% of patients on the first postoperative day. Other factors included noise from other patients and nursing staff, and using the toilet. Analgesia was taken by more than 90% of patients in the first two days, this number gradually reducing over the postoperative period. On the other hand, in the first two postoperative days, only about 5% of patients had night sedation. Discussion and conclusions: Apart from highlighting the need for effective pain management postoperatively, we believe that our study supports the drive towards single bed bays, where steps can be taken to minimize the impact of environmental factors on sleep. Highlights: This study is a prospective questionnaire survey of 102 surgical patients who procedures over a set time period. The aim of the study was to determine factors contributing to sleep deprivation postoperatively on a surgical ward. Unexpectedly, patients were not sleep deprived postoperatively but slept more during the daytime. Pain and noise were the main factors contributing to sleep deprivation. The authors then conclude that their study supports a drive towards single bed bays.